A PENGEMBANGAN MEDIA PEMBELAJARAN DASAR-DASAR OTOMOTIF SUB POKOK SISTEM REM BERBASIS TRAINER: PENGEMBANGAN MEDIA PEMBELAJARAN DASAR-DASAR OTOMOTIF SUB POKOK SISTEM REM BERBASIS TRAINER - I Made Satrya Adi Wibawa; Edi Elisa; Gede Widayana; Kadek Rihendra Dantes (Universitas Pendidikan Ganesha, 2026)
This study aims to develop a trainer-based learning medium for the brake system topic, determine the medium's feasibility, and assess its practicality. The study was motivated by the limited availability of practical learning media to assist students in understanding brake system concepts within the Automotive Fundamentals course at the Mechanical Engineering Education Study Program, Universitas Pendidikan Ganesha. The study employed the Research and Development (R&D) method using the 4D development model (Define, Design, Develop, and Disseminate); however, the research was conducted only up to the Develop stage. The research subjects consisted of two design experts, two manufacturing experts, 15 students for the small-group trial, and 30 students for the large-group trial. Data were collected via questionnaires and analyzed using quantitative descriptive analysis. The results indicated that the instrument's content validity score was 0.926, falling into the